Measurement of π⁰ photoproduction on the proton at MAMI C; Physical Review C - Nuclear Physics; Vol. 92, iss. 2 - Adlarson P.; Afzal F.; Akondi C. S.; Annand J. R. M.; Arends H. J.; Azimov Ya. I.; Beck R.; Borisov N.; Braghieri A.; Briscoe W. J.; Cherepnya S.; Cividini F.; et al. (2015, 2015)
Title screen